A study based on whole-genome sequencing yields a rare variant at 8q24 associated with prostate cancer - Gudmundsson, J; Sulem, P; Gudbjartsson, D; Masson, G; Agnarsson, B; Agnarsson, B; Benediktsdottir, K; Benediktsdottir, K; Sigurdsson, A; Magnusson, O; Gudjonsson, SA; Magnusdottir, D; et al. (2012)
In Western countries, prostate cancer is the most prevalent cancer of men and one of the leading causes of cancer-related death in men. Several genome-wide association studies have yielded numerous common variants conferring risk of prostate cancer. Here, we analyzed 32.5 million variants discovered by whole-genome sequencing 1,795 Icelanders. We identified a new low-frequency variant at 8q24 associated with prostate cancer in European populations, rs188140481[A] (odds ratio (OR) = 2.90; P combined = 6.2 × 10-34), with an average risk allele frequency in controls of 0.54%. This variant is only very weakly correlated (r 2 ≤ 0.06) with previously reported risk variants at 8q24, and its association remains significant after adjustment for all known risk-associated variants. Carriers of rs188140481[A] were diagnosed with prostate cancer 1.26 years younger than non-carriers (P = 0.0059). We also report results for a previously described HOXB13 variant (rs138213197[T]), confirming it as a prostate cancer risk variant in populations from across Europe. © 2012 Nature America, Inc. All rights reserved.